Decreased plasma levels of the brain-derived neurotrophic factor correlate with right heart congestion in pulmonary arterial hypertension. Issue 2 (6th March 2023) - Schäfer, Katharina; Tello, Khodr; Pak, Oleg; Richter, Manuel; Gierhardt, Mareike; Kwapiszewska, Grazyna; Veith, Christine; Fink, Ludger; Gall, Henning; Hecker, Matthias; Kojonazarov, Baktybek; Kraut, Simone; et al.
Background: The brain-derived neurotrophic factor (BDNF) may promote development of pulmonary hypertension and right ventricular (RV) failure. However, BDNF plasma levels were decreased in patients with left ventricular (LV) failure. Therefore, we investigated BDNF plasma levels in pulmonary hypertension patients and the role of BDNF in mouse models of pulmonary hypertension and isolated RV failure. Methods: BDNF plasma levels were correlated to pulmonary hypertension in two patient cohorts, including either post- and pre-capillary pulmonary hypertension patients (first cohort) or only pre-capillary pulmonary hypertension patients (second cohort). In the second cohort, RV dimensions and load-independent function were determined by imaging and pressure–volume catheter measurements, respectively. For induction of isolated RV pressure overload, heterozygous Bdnf knockout ( Bdnf +/− ) mice were subjected to pulmonary arterial banding (PAB). For induction of pulmonary hypertension, mice with inducible knockout of BDNF in smooth muscle cells ( Bdnf / Smmhc knockout) were exposed to chronic hypoxia. Results: Plasma BDNF levels were decreased in patients with pulmonary hypertension. Following adjustment for covariables, BDNF levels negatively correlated in both cohorts with central venous pressure. In the second cohort, BDNF levels additionally negatively correlated with RV dilatation. In animal models, BDNF downregulation attenuated RV dilatation in Bdnf + / − mice after PAB or hypoxic Bdnf / Smmhc knockout mice, although they developed pulmonary hypertension to a similar extent. Conclusions: Similar to LV failure, circulating levels of BDNF were decreased in pulmonary hypertension patients, and low BDNF levels were associated with right heart congestion. Decreased BDNF levels did not worsen RV dilatation in animal models, and thus, may be the consequence, but not the cause of RV dilatation. Plasma BDNF levels are decreased in IPAH patients, and correlate with central venous pressure and RV dilatation but not heart function. Low BDNF levels in animal models attenuate RV dilatation. https://bit.ly/3e2dwTK